# Describe the transformations of f(x)=sqrt[3]{x} and h(x)=x^{3} that result in the functions listed below. g(x)= -sqrt[3]{x - 3} and j(x)= -(x - 3)^{3} p(x)=4sqrt[3]{-x} - 1 and q(x)=0.25(-4x)^{3} - 1

Describe the transformations of
$f\left(x\right)=\sqrt{3}\left\{x\right\}$ and $h\left(x\right)={x}^{3}$
that result in the functions listed below.
and
and
You can still ask an expert for help

• Questions are typically answered in as fast as 30 minutes

Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it

broliY
Step 1
We are given the functions:
$f\left(x\right)=\sqrt{3}\left\{x\right\}$
$h\left(x\right)={x}^{3}$
Step 2
a) We write the transformations of the function $f\left(x\right)$ to reach
(shift to the right with 3 units)
(reflection in the x-axis)
Step 3
We write the transformations of the function $h\left(x\right)$ to reach :
(shift to the right with 3 units)
(reflection in the x-axis)
Step 4
b). We write the transformations of the function $f\left(x\right)$ to reach
(reflection in the y-axis)
(vertical strech)
(shift down with 1 unit)
Step 5
We write the transformations of the function $h\left(x\right)$ to reach
(horizontal shrink)
(reflection in they-axis)
(vertical shrink)
(shift down with 1 unit)